Faktor yang Berhubungan dengan Perilaku Perawat dalam Pemakaian APD di Ruang Rawat Inap Salah Satu Rumah Sakit Swasta di Yogyakarta - Mawarni, V.Endah; Widyastuti, Ch. Setya; Marti, Eva (STIKes Panti Rapih, 2021)
ABSTRACT Backround: Nurses' behavior in using PPE is considered very important in improvingthe quality of health services as well as the occupational safety and health of nurses inhospitals Objective: To determine the factors related to the behavior of nurses in nusing personal protective equipment in the inpatient unit Private Hospital at Yogyakarta. Methods: This study used a quantitative descriptive research design with a cross sectional approach, with a total sample of 30 respondents. The sample obtained by the total population technique. The data collection methods used were questionnaires and observations. Results: The study showed that most of the nurses had good enough behavior, 63,3%, almost half of them had good behavior, 33,3% and a small proportion of bad behaviorwas 3,3%. As much as 70% have good knowledge, a small proportion of knowledge isgood enough, 13,3% and a small proportion of knowledge is not good 16,7%. Most ofthe attitudes are quite positive 53,3%, almost half are positive attitudes are 40% and a small have negative attitudes 6,7%. Conclusion: It is hoped that the hospital will provide socialization and practice of usingPPI by PPI to inpatient room nurses once every 3 months and raise awareness and remind fellow nurses to wear PPE according to the SPO.